Revealing Prosodic Patterns of Emotional Expression of Mike, a Character with Cerebral Palsy in Triumph Movie - Ni Putu Dian Angga Melani; I Nyoman Suparwa; Ni Ketut Widhiarcani Matradewi (International Journal of Multilingual Education and Applied Linguistics, 2026)
Emotion is a natural aspect of human life, including that of individuals with Cerebral Palsy or CP. Generally, emotion can be triggered by situational factors and expressed through language, particularly through prosody. However, studies that explicitly link emotion, CP, and prosody remain limited. Therefore, this research aimed to identify the types of emotions experienced by Mike, a character with CP in theTriumph movie, as well as their prosodic performances. The research data consisted of Mike’s utterances and facial expressions, which were analyzed qualitatively using observation and documentation methods, along with note-taking and triangulation technique. The theories used were psycholinguistic, affective priming, and prosodic, that was also supported by Praat software. The findings showed that the emotions expressed by Mike included happiness (the most dominant), sadness, anger, surprise (the least frequent), and fear, which were triggered by social support or rejection from people around him. From a prosodic perspective, intonation and loudness exhibited contrasting patterns, resulting in varying degrees of word stress. Happiness was characterized by a pitch of 155.31 Hz and an intensity of 58.78 dB, sadness by a lower pitch of 148.54 Hz and the lowest intensity at 53.89 dB, anger by the highest pitch at 280.7 Hz and the strongest intensity at 62.47 dB, surprise by a pitch of 196.3 Hz and an intensity of 56.38 dB, and fear by a pitch of 161.03 Hz with an intensity of 57.97 dB.In sum, the results indicated a strong interrelationship between emotion and prosody in Mike’s speech.